PENGARUH METODE COOVERATIVE LEARNING TIPE ROUNDTABLE TERHADAP KEMAMPUAN MENULIS CERPEN PADA SISWA KELAS VII SMP ISLAM HEGARMANAH TAHUN PELAJARAN 2022-2023 - Krismiati, Aneu; Humaira, Hera Wahdah (Jurnal Ilmiah Wahana Pendidikan, 2024)
Education is a role that is very decisive for the development and quality of individuals, especially for the development of the nation and state. Indonesian language skills at school are implemented through Indonesian language subjects. Language learning cannot be separated from four skills, namely listening skills, speaking skills, reading skills, writing skills. In school learning, students are required to be skilled at writing so they can express ideas. One of the reasons learning outcomes are not optimal is that the learning model used is not appropriate to the material being discussed. This is the basis for researchers conducting research using the title "The Influence of the Round Table Type Cooperative Learning Model on the Short Story Writing Skills of Class VII Students of Hegarmanah Islamic Middle School".